2022
DOI: 10.3389/fnmol.2022.1023482
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exercise remodels the lysine acetylome in the mouse hippocampus

Abstract: Physical exercise benefits hippocampal function through various molecular mechanisms. Protein acetylation, a conserved and widespread post-translational modification, is involved in the synaptic plasticity and memory. However, whether exercise can change global acetylation and the role of acetylated proteins in the hippocampus have remained largely unknown. Herein, using healthy adult mice running for 6 weeks as exercise model and sedentary mice as control, we analyzed the hippocampal lysine acetylome and prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…Furthermore, our study revealed that, when exposed to CIH, Got2, a crucial enzyme involved in mitochondrial metabolism, undergoes acetylation at six lysine residues, K90, K82, K302, K309, K396, and K404. Our findings align with existing evidence that acetylation inhibits the activity of mitochondrial enzymes ( Qian et al, 2022 ). Moreover, our findings suggest that chronic intermittent hypoxia (CIH)-induced lysine acetylation may have detrimental effects on the mitochondrial tricarboxylic acid (TCA) cycle and oxidative phosphorylation pathways within the hippocampus.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, our study revealed that, when exposed to CIH, Got2, a crucial enzyme involved in mitochondrial metabolism, undergoes acetylation at six lysine residues, K90, K82, K302, K309, K396, and K404. Our findings align with existing evidence that acetylation inhibits the activity of mitochondrial enzymes ( Qian et al, 2022 ). Moreover, our findings suggest that chronic intermittent hypoxia (CIH)-induced lysine acetylation may have detrimental effects on the mitochondrial tricarboxylic acid (TCA) cycle and oxidative phosphorylation pathways within the hippocampus.…”
Section: Discussionsupporting
confidence: 92%
“…Once the beads were washed and the bound peptides were eluted using trifluoroacetic acid, we combined the eluted peptides, vacuum-dried them, desalted them, and prepared them for analysis. More specific formulations for the inhibitors and NETN buffer can be found elsewhere ( Qian et al, 2022 ). LC-MS/MS analysis was conducted at PTM Biolab in Hangzhou, China.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sequence model composed of specific amino acids was analyzed by Motif-x (10 amino acids downstream and upstream of crotonylation sites). Once protein enrichment was completed, function x = 2log 10 (p value) ran to convert the p value and one-way hierarchical clustering to category (Qian et al, 2022).…”
Section: Bioinformatics Analysismentioning
confidence: 99%
“…Enrichment of differentially modified proteins relevant to all identified proteins for each category of GO analysis, including cellular compartment, biological process, and molecular function was detected in two-tailed Fisher's exact test. We considered GO terms significant at a corrected p < 0.05 and used DAVID 6.8 to perform GO term enrichment (Qian et al, 2022).…”
Section: Tandem Mass Tagging Proteomic Analysismentioning
confidence: 99%